Car crash detector system/ Mohd Shahril Mat Saad - Mat Saad, Mohd Shahril (2009)
This thesis proposes a new technology of the safety system that called car crash detector. The sensor will detect the impact of collision and send the signal to the system. The system will automatically tum off the engine if met the condition. This can avoid the car from burning or get exploded. The system also prevent the airbag to activate when the collision give low impact. Programmable Interface Controller (PIC) is use as an interface between the input (sensor) and output (engine system) and the PIC used in this project is PICl 8F4550. In this thesis, the whole project will be described briefly in each chapter. The system use distance detector or distance sensor type to detect the distance changes on the front of the car. The change of the distance that varies by speed is considered to make sure the correct programming code can be written in the PIC. In Chapter 2, the theoretical aspect regarding the PIC l 8F4550 microcontroller, sensor and voltage regulator will be presented and explained for further understanding. In Chapter 3, the measure Development for Car Crash Detector System hardware and software designs are explained. The technical aspects are discussed with the aid of the schematic design. The analyzing of the results and discussions are presented in Chapter 4. Finally, the conclusion and future developments are stated in Chapter 5.